Travis Jenks: capstone - Jenks, Travis, artist (Colorado State University. Libraries, 2015)
The artist's statement: The majority of my work over the past few years has begun with some sort of direction, whether it be a given project or idea, I always get a starting point from somewhere or something. After that, I take to the internet for research and inspiration. I've been interested in a multitude of different design styles over the years and I believe a lot of it shows up in my work, even if the majority of it is under the same branding guide. As a graphic designer, it can be hard to say where my inspiration comes piece by piece, when I am a graphic designer simply because I love it. Each project has a different inspiration, whether it is something I saw at the time, or something I've seen and wanted to replicate. It has truly been wonderful finding my passion and purpose.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design